Additional records of Norwegian skate Dipturus nidarosiensis (Storm, 1881) (Pisces: Rajidae) in the Adriatic Sea - Isajlović, Igor; Dulčić, Jakov; Piccinetti, Corrado; Vrgoč, Nedo; Manfredi, Chiara; Dragičević, Branko (2020)
Additional records of the Norwegian skate Dipturus nidarosiensis (Storm, 1881)from the Adri-atic Sea are reported. Two specimens were collected in the southern Adriatic Pit in 2008 and 2010, respectively. The records reported herein improve our knowledge on the distribution of a rarely encountered, deep water species D. nidarosiensis, whose presence has only recently been confirmed in the Mediterranean Sea.
U radu su opisani novi nalazi crne voline Dipturus nidarosiensis (Storm, 1881) iz Jadran-skoga mora. Dva primjerka ulovljena su na području Južnojadranske kotline 2008. odnosno 2010. godine. Ovi nalazi proširuju saznanja o distribuciji ove rijetke dubokomorske vrste čija je prisutnost u Sredozemnom moru tek nedavno utvrđena.
Bibliografija: str. 220-222.
Summary ; Sažetak.
Keywords: Crna volina -- Dipturus nidarosiensis -- Novi nalaz; Jadransko more -- Sredozemno more